2007
DOI: 10.1111/j.1365-2427.2006.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative states in the phytoplankton of Lake Kinneret, Israel (Sea of Galilee)

Abstract: 1. Through analyses of a 34-year record of phytoplankton, zooplankton and physicochemical parameters from Lake Kinneret, Israel, we show that distinct and persistent phytoplankton assemblage states occurred from winter to summer. 2. The most obvious characteristic of these states was the presence or absence of a spring bloom of the dinoflagellate, Peridinium gatunense. 3. Analyses of the data within the framework of the alternative states model revealed a possible complex triggering mechanism, and system hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 68 publications
(101 reference statements)
3
36
0
Order By: Relevance
“…Since the mid-1990s, intense Peridinium blooms have occurred only in years of higher than average inflow volumes and as a result of higher nutrient loading (Zohary 2010). On the other hand, explanations for absence of bloom include the epidemic infection of chytrid fungi (Alster and Zohary 2007) as well as higher long-term rises in temperature, which give a competitive advantage to green algae, which have a faster growth rate (Roelke et al 2007). The findings from this study suggest that lake circulation effects also need to be considered, particularly the timing of stratification, wind forcing, and resonance.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-1990s, intense Peridinium blooms have occurred only in years of higher than average inflow volumes and as a result of higher nutrient loading (Zohary 2010). On the other hand, explanations for absence of bloom include the epidemic infection of chytrid fungi (Alster and Zohary 2007) as well as higher long-term rises in temperature, which give a competitive advantage to green algae, which have a faster growth rate (Roelke et al 2007). The findings from this study suggest that lake circulation effects also need to be considered, particularly the timing of stratification, wind forcing, and resonance.…”
Section: Discussionmentioning
confidence: 99%
“…Berman et al (1995) concluded that the lake showed remarkable stability from 1970 to 1993 despite considerable environmental changes, population growth and intense economic development. Later studies, based on longer records (Zohary, 2004;Roelke et al, 2007), have concluded that the lake has become considerably less stable since the mid1990s, following a 4 m rise in water level over a single winter (1991)(1992) recorded for the first time. Not only did Peridinium fail to bloom every year and cyanobacteria became dominant in summer, but the summer assemblage also changed, with filamentous morphotypes becoming dominant as opposed to the nanoplanktonic unicells and coenobia that dominated in the past.…”
Section: Case Studiesmentioning
confidence: 99%
“…Although the commercial fisheries of Lake Kinneret have been regulated since the 1930s (Ben-Tuvia et al 1992), harvest in the dominant Kinneret bleak fishery shifted to larger sizes beginning in 1985 and resulted in long-term overharvest, reduction of mean body sizes, and eventual collapse of the fishery in 1993 (Hambright and Shapiro 1997). The resulting smaller mean body sizes in the bleak population (Ostrovsky and Walline 2001) yielded increased predation pressure on zooplankton (sensu Brown et al 2004), leading to reduced zooplankton biomass and mean body sizes, and possibly further food-web alterations (Roelke et al 2007;K. D. Hambright, unpublished manuscript).…”
Section: Historical Natural and Anthropogenic Eventsmentioning
confidence: 99%
“…Such high variability is characteristic of other ecosystem destabilizations that result from human-induced lake eutrophication (Schindler 1987, Cottingham et al 2000, Carpenter 2005. Explicit reasons for these dramatic developments are unproven, although increased external and internal nutrient influx, modified lake hydrology, and inappropriate fisheries practices may have been involved , Roelke et al 2007). …”
Section: Introductionmentioning
confidence: 99%